(untitled) (Modern information system and technologies, 2018)
The article deals with heuristic approaches in the management of complex technical systems. The purpose of the work is to investigate heuristic methods for control systems, to create a heuristic model for managing irrigation systems. Methods of development include studying the material, a heuristic approach - the method of empathy or personal analogy.